The Role of Green Intellectual Capital in Developing Advanced Waste-to-Energy Technologies : An Analysis of Incineration Plant Experiences in the Iraq - Ahmed Shaker Hamad (International Forum of Researchers and Lecturers, 2025)
The purpose of this paper is to examine the role of Green Intellectual Capital (GIC) in the development of waste-to-energy (WtE) technologies, which is of special relevance for the incineration plants in the Gulf Cooperation Council (GCC) countries. Although previous studies have focused primarily on technological and infrastructural aspects, this paper investigates the contribution of intangible assets such as green human, structural, and relational capital towards the performance and sustainability of WtE systems. Adopting a mixed-method approach, the results show that Green Structural Capital has the first place in supporting operational efficiency, followed by Green Human Capital and Green Relational Capital. The statistical analysis based on Structural Equation Modeling (SEM) shows that all GIC dimensions are positively related to plant performance, with institutionalized knowledge and systems as the most significant enablers of innovation. Qualitative findings also highlight constraints such as lack of training, unhandy knowledge systems, and poor public-private interaction. The findings recommend policy suggestions for promoting GIC assimilation within environmental infrastructure and provide a region-based theoretical model connecting knowledge-based resources and sustainable waste management practices. The study emphasizes the importance of integrating intellectual capital into the strategic decision-making process of waste-to-energy plants to enhance their operational effectiveness and long-term sustainability. Additionally, the research underlines that fostering a knowledge-sharing culture and enhancing collaboration between various stakeholders, including governmental bodies, private firms, and research institutions, is critical for the success of green initiatives. Training programs aimed at developing green human capital and improving public-private partnerships are essential to overcoming the current barriers to innovation in the WtE sector. This study has practical and scholarly implications in unifying the focus from just technology to the facilitating role of human and intellectual capital in green transformation, further bridging the gap between environmental sustainability and technological advancements in waste management.